Water Balance Analysis Using the Thornthwaite-Mather Method as a Basis for Cropping Pattern Development in Dry Land - Sophia Dwiratna; Yogina Lestari Ayu; Chay Asdak; Nabila Aura Pithaloka (The University of Lampung, 2025)
Soil water availability is crucial for supporting plant growth, especially in drylands that rely on rainfall as the primary source to meet plant water needs. Rainfall variability complicates the prediction of planting times and the optimization of cropping patterns. This condition negatively impacts productivity and increases the risk of flooding and landslides. This study aims to analyze the land water balance using the Thornthwaite Mather method on nine existing planting patterns and schedules, and to recommend strategies that can be implemented to prevent water deficit conditions. A descriptive method with a quantitative approach was used to analyze agroclimatic data to identify periods of water surplus and deficit. The results of the water balance analysis show that water surplus occurs from November to May, while deficit occurs from June to October. Conservation strategies, such as rainwater harvesting through microcatchment and macrocatchment systems, are proposed as effective approaches to address water deficit. These strategies can increase water availability, reduce the risk of crop failure, and optimize the use of available water resources. This study is expected to serve as a foundation for developing adaptive cropping patterns and enhancing the sustainability of the agricultural sector in the face of climate change. Keywords: Dry land, Rainwater harvesting, Thornthwaite-Mather, Water balance, Water management.